2020
DOI: 10.4081/jphr.2020.1747
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Smoke-Free Law in Denpasar Bali: Between Compliance and Social Norms of Smoking

Abstract: Background: Since 2013, City of Denpasar government has adopted a smoke-free law. Implementation of the law faces several obstacles, partly due to the high social acceptability of smoking in the city, where cigarette and smoking has been deeply engrained within social life and become part of hospitality. This study aims to assess the smoke-free law compliance and to explore the social norms that may affect the compliance. Design and Methods: The study was a mix of cross-sectional compliance survey and qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Support for SFPs from hotel management plays an important role in increasing compliance (Devhy et al, 2014). Nevertheless, this compliance is also influenced by political and government commitment (Asyary & Veruswati, 2018;Robertson et al, 2018) as well as individual awareness (Robertson et al, 2018;Suarjana et al, 2020;Wahyuti et al, 2019). Most hospitality managers in this study found that customer resistance, unclear sanctions, and a lack of socialization from the government were three interconnected obstacles to enforcing SFPs.…”
Section: Discussionmentioning
confidence: 82%
“…Support for SFPs from hotel management plays an important role in increasing compliance (Devhy et al, 2014). Nevertheless, this compliance is also influenced by political and government commitment (Asyary & Veruswati, 2018;Robertson et al, 2018) as well as individual awareness (Robertson et al, 2018;Suarjana et al, 2020;Wahyuti et al, 2019). Most hospitality managers in this study found that customer resistance, unclear sanctions, and a lack of socialization from the government were three interconnected obstacles to enforcing SFPs.…”
Section: Discussionmentioning
confidence: 82%
“…From the included studies, the highest non-compliance with smoke-free law was found to be 98.2% in food and drinking establishments ( 32 ) and the lowest non-compliance was 10.3% in healthcare facilities ( 36 ). Regarding the study country, four studies were conducted in India ( 29 , 31 , 35 , 37 ), two in China ( 17 , 30 ), two in Russia ( 28 , 38 ), one in United states ( 15 ), one in Guatemala ( 24 ) one in Indonesia ( 16 ), two in Ethiopia ( 14 , 36 ), two in South Africa ( 23 , 32 ), one in Australia ( 19 ), one in Portugal ( 34 ), one in European Union ( 27 ), one in Bangladesh ( 26 ), one in Vietnam ( 33 ), one in Turkey ( 22 ), one in Pakistan ( 21 ), and one in Nepal ( 25 ). Among the included the studies, the sample size ranged between 25,475,032 ( 15 ) and 40 ( 37 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding methods of data collection, thirteen studies collected data using observational methods ( 14 , 16 , 21 , 25 , 26 , 29 , 30 , 32–37 ), five studies using review report ( 15 , 23 , 28 , 31 , 38 ), three studies using self-administered questionnaire ( 17 , 19 , 27 ), one study using both observational and interview ( 22 ), and one study collected using data measuring ( 24 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visually, the installation of a no-smoking sign is also very important to raise public awareness for law and order, and not smoking in public facilities. 16 The fourth indicator was no cooperation with tobacco industries, with an estimated CFA value of -.056 meaning that this indicator does not shape the level of SFA implementation. When the public facility cooperates with the tobacco industry it does not mean that the facility does not comply with regulations in a smoke-free area.…”
Section: Dicussionmentioning
confidence: 99%